Hydroxyl radical-induced formation of highly oxidized organic compounds - Torsten Berndt; Stefanie Richters; Tuija Jokinen; Noora Hyttinen; Theo Kurtén; Rasmus V. Otkjær; Henrik G. Kjaergaard; Frank Stratmann; Hartmut Herrmann; Mikko Sipilä; Markku Kulmala; Mikael Ehn (Nature Communications, 2016)
Secondary organic aerosols are important contributors to the Earth’s radiation budget, however questions remain about their formation from highly-oxidized precursors. Here the authors show that the daytime reaction of hydroxyl radicals with α- and β-pinene is a greater source of highly-oxidized products than previously assumed.